Mystical Astronomy in Ethiopian Orthodoxy: Monastic Insights into the Cosmos and Divine Order - Belay Sitotaw Goshu; Muhammad Ridwan (Britain International for Academic Research (BIAR-Publisher), 2025)
absatau